1. PERDAGANGAN PEREMPUAN VIETNAM KE TIONGKOK TAHUN 2005-2009: PERSPEKTIF FEMINISME-SOSIALIS - Lestari, Dwi Ayu (Journal of International Relations, 2017)
Woman trafficking in Vietnam was a transnational crime in which the victim experienced sexual exploitation, either for porstitution or forced marriage. This study aimed to explain the case of woman traffickingin Vietnam to China 2005-2009. This study employed socialist feminism theory along with qualitative methods through interviews, and literature research. This study also found that women trafficking in Vietnam caused by the culture of patriarchy in both Vietnam and China. In both countries women were considered as a second class that made them, underwent social and economic discrimination. Consequently, the vunerability of women trafficking abroad was significantly increased.